Diagnosing Diabetic Foot Osteomyelitis in Patients Without Signs of Soft Tissue Infection by Coupling Hybrid (67)Ga SPECT/CT With Bedside Percutaneous Bone Puncture - Aslangul, Elisabeth (American Diabetes Association, 2013)
OBJECTIVE: Successful treatment of osteomyelitis is more likely with accurate diagnosis and identification of the causative pathogens. This typically requires obtaining a specimen of bone, usually by image-guided biopsy. We sought to develop a simpler bedside method for definitively diagnosing osteomyelitis. RESEARCH DESIGN AND METHODS: Over 2 years, we enrolled consecutive patients presenting to our diabetic foot clinic with a foot ulcer and clinically suspected osteomyelitis but without soft tissue infection. Each underwent hybrid (67)Ga single-photon emission computed tomography and X-ray computed tomography (SPECT/CT) imaging; those with a positive scan underwent bedside percutaneous bone puncture. Patients with a positive bone culture received culture-guided antibiotic therapy. Patients with negative (67)Ga SPECT/CT imaging or with positive imaging but negative bone culture were not treated with antibiotics. All patients were followed up for ≥1 year. RESULTS: Among 55 patients who underwent (67)Ga SPECT/CT imaging, 13 had negative results and all of their foot ulcers resolved without antibiotic therapy. Among 42 with positive imaging, 2 were excluded (for recent antibiotic therapy) and 40 had bone punctures (3 punctured twice): 19 had negative results, 3 of which were likely false negatives, and 24 had positive results (all gram-positive cocci). At follow-up, 3 patients had died, 3 had undergone amputation, and 47 had no evidence of foot infection. The sensitivity and specificity of this combined method were 88.0 and 93.6%, respectively, and the positive and negative predictive values were 91.7 and 90.7%, respectively. CONCLUSIONS: Coupling of (67)Ga SPECT/CT imaging and bedside percutaneous bone puncture appears to be accurate and safe for diagnosing diabetic foot osteomyelitis in patients without signs of soft tissue infection, obviating the need for antibiotic treatment in 55% of suspected cases.